Educational deprivation in Latin America: Structural inequality beyond borders - Sánchez-Restrepo, H.; Louçã, J. (Advances in human factors in training, education, and learning sciences. Advances in intelligent systems and computing, 2020)
This is a secondary research that uses the results of a large-scale assessment to those children attending school in sixth grade, coordinated by UNESCO in 15 Latin American countries, for estimating the level of learning achievements in the scientific domain. The quality of the data allows estimating deprivation of learning in each country, offering high-level evidence on the deep lack of equity in educational systems and unveiling the structure of learning inequality through statistical and network analysis. This study offers unique evidences about the inequality gaps in learning outcomes and the incidence of educational deprivation for improving empirical knowledge about the regional interdependence between learning, cultural capital and the socioeconomic status of student’s families. In addition, this contribution provides new tools to the current theoretical framework for assessing the challenges faced by the countries in the region and establishes three milestones in educational research. The first one is to provide a direct method to estimate educational deprivation. The second one is to recognize the structure of inequality through decomposition in regional socioeconomic groups with comparable measures. The third one is estimating learning gaps and their association with the socioeconomic status of students’ families beyond borders.